Nursing care for patients with heart failure: An integrative review - Mello, Déborah Lima de; Pereira, Denise Andrade; Souza, Ana Beatriz Floriano de (Seven Editora, 2024)
Introduction: Heart Failure (HF) is a complex clinical syndrome in which the heart is ventricular involved and unable to meet the body's metabolic demands. In Brazil, the main cause of rehospitalizations is due to difficulties in adhering to the therapy implemented. Objective: To provide evidence of nursing care for HF patients based on scientific publications. Method: This is an integrative review of the literature, developed from searches in the National Library of Medicine (PubMed), Web of Science and Virtual Health Library (VHL) databases. To elaborate the guiding question, the PICo strategy was used. Thus, the following guiding question was defined: what does the scientific evidence available in the literature address about nursing care for patients with heart failure? Searches were limited to the period between 2018 and 2023, in the languages Portuguese, Spanish and English. Results: The final sample consisted of nine articles, out of a total of 2,579 initially listed. The studies were grouped by similarities, defining the following categories: Marjory Gordon and Callista Roy's models of care, health education, and the use of technologies in self-management and HF monitoring. Conclusions : This study made it possible to analyze what the scientific evidence addresses about nursing care for patients with HF. It has been demonstrated that further research is needed on this topic, since HF is prevalent in thousands of individuals around the world and that some of them do not fully understand the diagnosis, symptoms, self-care and the importance of treatment adherence. DOI:https://doi.org/10.56238/sevened2024.007-063